Responder
The solutions to the equations are:
1. \( x=14 \)
2. \( x=\frac{4}{3} \) or \( x=1.3 \)
3. \( x=-3 \) or \( x=3 \)
4. \( x=3 \)
5. \( x=4 \)
6. \( x=1 \) or \( x=\frac{4}{3} \)
Solución
Solve the equation \( \sqrt{x+2}=4 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\sqrt{x+2}=4\)
- step1: Find the domain:
\(\sqrt{x+2}=4,x\geq -2\)
- step2: Raise both sides to the \(2\)-th power\(:\)
\(\left(\sqrt{x+2}\right)^{2}=4^{2}\)
- step3: Evaluate the power:
\(x+2=16\)
- step4: Move the constant to the right side:
\(x=16-2\)
- step5: Subtract the numbers:
\(x=14\)
- step6: Check if the solution is in the defined range:
\(x=14,x\geq -2\)
- step7: Find the intersection:
\(x=14\)
- step8: Check the solution:
\(x=14\)
Solve the equation \( 3 \sqrt{x}=2 \sqrt{3} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(3\sqrt{x}=2\sqrt{3}\)
- step1: Find the domain:
\(3\sqrt{x}=2\sqrt{3},x\geq 0\)
- step2: Divide both sides:
\(\frac{3\sqrt{x}}{3}=\frac{2\sqrt{3}}{3}\)
- step3: Divide the numbers:
\(\sqrt{x}=\frac{2\sqrt{3}}{3}\)
- step4: Raise both sides to the \(2\)-th power\(:\)
\(\left(\sqrt{x}\right)^{2}=\left(\frac{2\sqrt{3}}{3}\right)^{2}\)
- step5: Evaluate the power:
\(x=\frac{4}{3}\)
- step6: Check if the solution is in the defined range:
\(x=\frac{4}{3},x\geq 0\)
- step7: Find the intersection:
\(x=\frac{4}{3}\)
- step8: Check the solution:
\(x=\frac{4}{3}\)
Solve the equation \( \sqrt{x^{2}+7}-4=0 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\sqrt{x^{2}+7}-4=0\)
- step1: Move the constant to the right side:
\(\sqrt{x^{2}+7}=0+4\)
- step2: Remove 0:
\(\sqrt{x^{2}+7}=4\)
- step3: Raise both sides to the \(2\)-th power\(:\)
\(\left(\sqrt{x^{2}+7}\right)^{2}=4^{2}\)
- step4: Evaluate the power:
\(x^{2}+7=16\)
- step5: Move the constant to the right side:
\(x^{2}=16-7\)
- step6: Subtract the numbers:
\(x^{2}=9\)
- step7: Simplify the expression:
\(x=\pm \sqrt{9}\)
- step8: Simplify:
\(x=\pm 3\)
- step9: Separate into possible cases:
\(\begin{align}&x=3\\&x=-3\end{align}\)
- step10: Check the solution:
\(\begin{align}&x=3\\&x=-3\end{align}\)
- step11: Rewrite:
\(x_{1}=-3,x_{2}=3\)
Solve the equation \( \sqrt{x-2}=4-x \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\sqrt{x-2}=4-x\)
- step1: Find the domain:
\(\sqrt{x-2}=4-x ,x\geq 2\)
- step2: Evaluate:
\(\sqrt{x-2}=4-x,4-x\geq 0\)
- step3: Evaluate:
\(\sqrt{x-2}=4-x,x\leq 4\)
- step4: Solve the equation:
\(\begin{align}&x=6\\&x=3\end{align},x\leq 4\)
- step5: Find the intersection:
\(x=3\)
- step6: Check if the solution is in the defined range:
\(x=3,x\geq 2\)
- step7: Find the intersection:
\(x=3\)
- step8: Check the solution:
\(x=3\)
Solve the equation \( \sqrt{3 x+13}-1=x \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\sqrt{3x+13}-1=x\)
- step1: Find the domain:
\(\sqrt{3x+13}-1=x ,x\geq -\frac{13}{3}\)
- step2: Move the constant to the right-hand side:
\(\sqrt{3x+13}=x+1\)
- step3: Evaluate:
\(\sqrt{3x+13}=x+1,x+1\geq 0\)
- step4: Evaluate:
\(\sqrt{3x+13}=x+1,x\geq -1\)
- step5: Solve the equation:
\(\begin{align}&x=4\\&x=-3\end{align},x\geq -1\)
- step6: Find the intersection:
\(x=4\)
- step7: Check if the solution is in the defined range:
\(x=4,x\geq -\frac{13}{3}\)
- step8: Find the intersection:
\(x=4\)
- step9: Check the solution:
\(x=4\)
Solve the equation \( \sqrt{4-3 x}=4-3 x \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\sqrt{4-3x}=4-3x\)
- step1: Find the domain:
\(\sqrt{4-3x}=4-3x ,x\leq \frac{4}{3}\)
- step2: Evaluate:
\(\sqrt{4-3x}=4-3x,4-3x\geq 0\)
- step3: Evaluate:
\(\sqrt{4-3x}=4-3x,x\leq \frac{4}{3}\)
- step4: Solve the equation:
\(\begin{align}&x=1\\&x=\frac{4}{3}\end{align},x\leq \frac{4}{3}\)
- step5: Find the intersection:
\(\begin{align}&x=1\\&x=\frac{4}{3}\end{align}\)
- step6: Check the solution:
\(\begin{align}&x=1\\&x=\frac{4}{3}\end{align}\)
- step7: Rewrite:
\(x_{1}=1,x_{2}=\frac{4}{3}\)
The solutions to the given equations are:
1. \( \sqrt{x+2}=4 \) has the solution \( x=14 \).
2. \( 3 \sqrt{x}=2 \sqrt{3} \) has the solutions \( x=\frac{4}{3} \) or \( x=1.3 \).
3. \( \sqrt{x^{2}+7}-4=0 \) has the solutions \( x=-3 \) or \( x=3 \).
4. \( \sqrt{x-2}=4-x \) has the solution \( x=3 \).
5. \( \sqrt{3 x+13}-1=x \) has the solution \( x=4 \).
6. \( \sqrt{4-3 x}=4-3 x \) has the solutions \( x=1 \) or \( x=\frac{4}{3} \).
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución